Perceptions of family history and genetic testing and feasibility of pedigree development among African Americans with hypertension - Pettey, Christina M (Eur J Cardiovasc Nurs, 2014)
BACKGROUND: Pedigree development, family history, and genetic testing are thought to be useful in improving outcomes of chronic illnesses such as hypertension (HTN). However, the clinical utility of pedigree development is still unknown. Further, little is known about African Americans’ (AAs’) perceptions of family history and genetic testing. AIMS: This study examined the feasibility of developing pedigrees for AAs with HTN and explored perceptions of family history and genetic research among AAs with HTN. METHODS: The US Surgeon General’s My Family Health Portrait was administered, and 30–60 minute in-person individual interviews were conducted. Descriptive statistics were used to analyze pedigree data. Interview transcripts were analyzed with content analysis and constant comparison. RESULTS: Twenty-nine AAs with HTN were recruited from one free clinic (15 women, 14 men; mean age 49 years, SD 9.6). Twenty-six (90%) reported their family history in sufficient detail to develop a pedigree. Perceptions of family history included knowledge of HTN in the family, culturally influenced family teaching about HTN, and response to family history of HTN. Most participants agreed to future genetic testing and DNA collection because they wanted to help others; some said they needed more information and others expressed a concern for privacy. CONCLUSION: The majority of AAs in this sample possessed extensive knowledge of HTN within their family and were able to develop a three generation pedigree with assistance. The majority were willing to participate in future genetic research.